Analysis of the Use of Discretionary Rights in the Implementation of Regional Elections - Elisabeth DAN; Wilma Silalahi (Universitas Islam Sultan Agung, 2025)
Democracy is a system of governance that places the people as the ultimate holders of political authority. One of its primary manifestations is the mechanism of general elections, including local elections (Pilkada). Pilkada represents a concrete form of democracy at the regional level, allowing citizens to determine their local leaders. In practice, however, election administrators may confront circumstances that are not clearly regulated. In such situations, discretionary right becomes relevant to enable decision-making in the face of legal gaps or ambiguities, provided that it aligns with the general principles of good governance. This study aims to analyze the use of discretion by the Banjarbaru City General Election Commission (KPU Kota Banjarbaru) as the election management body in the 2024 mayoral and vice-mayoral election. The research method was used normative (doctrinal). The novelty in this research is the need to address specific situations, such as those encountered during the Pilkada implementation phase, by examining the 2024 simultaneous Pilkada in Banjarbaru City. Based on the research concluded that KPU’s decision to continue using the original ballotlisting two candidate pairs despite the disqualification of one pair and to classify votes for the disqualified candidate as invalid without clear differentiation constitutes an improper exercise of discretion. This decision neglected the principles of public interest, legal certainty, justice, and the protection of citizens’ electoral rights. The KPU’s inaccurate use of outdated ballots resulted in ambiguity regarding vote status, violations of fairness and electoral validity, and a decline in public trust in the integrity of the election process.